Relevansi Hadis tentang Ghibah terhadap Fenomena Ujaran Kebencian di Media Sosial: Analisis Tematik dan Etika Digital Muslim - Nasrulloh; Adzrah Dwi Sunarty Abas (LPPM IAI Hasanuddin Pare-Kediri, 2025)
This study examines the relevance of prophetic teachings on ghibah or backbiting in addressing the rising phenomenon of hate speech on social media. The research uses a qualitative library based design supported by thematic analysis to examine primary hadith sources and contemporary scholarly discussions. The findings show that ghibah in the digital age appears in new forms such as public shaming, mocking comments, cyberbullying, and the rapid circulation of unverified information, all of which correspond to the moral concerns presented in hadith literature. The study also reveals that integrating hadith based ethics with digital literacy, particularly the principle of tabayyun or information verification, provides a constructive moral framework for reducing harmful online behavior. In conclusion, this research emphasizes that prophetic ethics offer conceptual insight as well as practical guidance for fostering responsible, respectful, and ethical digital conduct among Muslim users.